Serological survey on immunity status against polioviruses in children and adolescents living in a border region, Apulia (Southern Italy) - Tafuri, Silvio (BioMed Central, 2008)
BACKGROUND: In 1988 the World Health Assembly adopted the goal to eradicate poliomyelitis by routine immunization using Oral Polio Vaccine (OPV). On 21 June 2002 the WHO European Region was declared polio-free. In 2008 poliomyelitis is still endemic in 4 countries (Nigeria, India, Pakistan, and Afghanistan), where 1201 new cases were registered in 2007; 107 sporadic cases were also notified in countries where poliovirus is not endemic. The aim of this work was to verify the level of antipoliomyelitis immunity status in children and adolescents in the Apulia region (south of Italy), which may be considered a border region due to its position. METHODS: 704 blood specimens from a convenience sample were collected in six laboratories. The age of subjects enrolled was 0–15 years. The immunity against poliomyelitis was evaluated by neutralizing antibody titration in tissue culture microplates. RESULTS: Seropositivity (neutralising antibodies titre ≥ 8) for polioviruses 1, 2 and 3 was detected in 100%, 99.8% and 99.4% of collected sera. Antibody titres were not lower in subjects who received either four doses of inactivated polio vaccine (IPV) or a sequential schedule consisting of two doses of IPV and two of oral polio vaccine than in subjects who received four doses of OPV. CONCLUSION: These results confirmed current data of vaccine coverage for poliomyelitis: during the last ten years in Apulia, the coverage in 24 months old children was more than 90%. The high level of immunization found confirms the effectiveness both of the sequential schedule IPV-OPV and of the schedule all-IPV. Apulia region has to face daily arrivals of refugees and remains subject to the risk of the importation of poliovirus from endemic areas. Surveys aimed at determining anti-polio immunity in subpopulations as well as in the general population should be carried out.